Extrafoveal Cone Packing in Eyes With a History of Retinopathy of Prematurity - Ramamirtham, Ramkumar (Invest Ophthalmol Vis Sci, 2016)
PURPOSE: To study the density and packing geometry of the extrafoveal cone photoreceptors in eyes with a history of retinopathy of prematurity (ROP). We used a multimodal combination of adaptive optics (AO) scanning light ophthalmoscopy (SLO) and optical coherence tomography (OCT). METHODS: Cones were identified in subjects (aged 14–26 years) with a history of ROP that was either severe and treated by laser ablation of avascular peripheral retina (TROP; n = 5) or mild and spontaneously resolved, untreated (UROP; n = 5), and in term-born controls (CT; n = 8). The AO-SLO images were obtained at temporal eccentricities 4.5°, 9°, 13.5°, and 18° using both confocal and offset apertures with simultaneous, colocal OCT images. Effects of group, eccentricity, and aperture were evaluated and the modalities compared. RESULTS: In the SLO images, cone density was lower and the packing pattern less regular in TROP, relative to CT and UROP retinae. Although SLO image quality appeared lower in TROP, root mean square (RMS) wavefront error did not differ among the groups. In TROP eyes, cone discrimination was easier in offset aperture images. There was no evidence of cone loss in the TROP OCT images. CONCLUSIONS: Low cone density in TROP confocal SLO images may have resulted from lower image quality. Since AO correction in these eyes was equivalent to that of the control group, and OCT imaging showed no significant cone loss, the optical properties of the inner retina or properties of the cones themselves are likely altered in a way that affects photoreceptor imaging.